The mild phenotype in severe hemophilia A with Arg1781His mutation is associated with enhanced binding affinity of factor VIII for factor X - Yada, Koji; Nogami, Keiji; Wakabayashi, Hironao; Fay, Philip J.; Shima, Midori (Thrombosis and Haemostasis, 2013)
The clinical severity in some patients with haemophilia A appears to be unrelated to the levels of factor (F)VIII activity (FVIII:C), but mechanisms are poorly understood. We have investigated a patient with a FVIII gene mutation at Arg1781 to His (R1781H) presenting with a mild phenotype despite FVIII:C of 0.9 IU/dl. Rotational thromboelastometry using the patient’s whole blood demonstrated that the clot time and clot firmness were comparable to those usually observed at FVIII:C 5–10 IU/dl. Thrombin and FXa assays using plasma samples also showed that the peak levels of thrombin formation and the initial rate of FXa generation were comparable to those observed at FVIII:C 5–10 IU/dl. The results suggested a significantly greater haemostatic potential in this individual than in those with severe phenotype. The addition of incremental amounts of FX to control plasma with FVIII:C 0.9 IU/dl in clot waveform analyses suggested that the enhanced functional tenase assembly might have been related to changes in association between FVIII and FX. To further investigate this mechanism, we prepared a stably expressed, recombinant, B-domainless FVIII R1781H mutant. Thrombin generation assays using mixtures of control plasma and FVIII revealed that the coagulation function observed with the R1781H mutant (0.9 IU/dl) was comparable to that seen with wild-type FVIII:C at ∼5 IU/dl. In addition, the R1781H mutant demonstrated an ∼1.9-fold decrease in Km for FX compared to wild type. These results indicated that relatively enhanced binding affinity of FVIII R1781H for FX appeared to moderate the severity of the haemophilia A phenotype.Note: An account of this work was presented, in part, at the 23rd Congress of the International Society of Thrombosis and Haemostasis, July 27, 2011, Kyoto, Japan.
Keywords: Haemophilia A; FVIII; clinical phenotype; FX; association